«Gold cells» of virtual learning environments - A. . Solovov (Высшее образование в России)
The article focuses on the main differences between organizational forms of traditionaland e-learning. Discusses the need for regulation of formal education and the facilities of virtual learning environments. Provides guidelines for forming the rational structure of a distance course model, evaluates the prospects of using the cloud services in education.